THE EFFECTS OF STUDENTS’ PERCEPTION ON USING TEACHING MEDIA AND VOCABULARY MASTER ON STUDENTS’ LISTENING SKILL - Desi Adrianty; Syahfitri Purnama (INFERENCE: Journal of English Language Teaching, 2019)
Abstract: This research aims to know the effect of students’ perception of learning media and vocabulary mastery toward students’ listening comprehension skills. The result of the research shows that; 1). There are significant effects of students’ perception on the use of learning media and vocabulary mastery toward students’ listening comprehension skills at the Private Colleges in Jakarta.  The significant effect was proved by the score of Sig. = 0,000< 0,05 andF0= 47.238. Both variables, the students’ perception on the use of learning media and vocabulary mastery, had a contribution of 62.4 % to the students’ listening comprehension. 2). There is a significant effect of the students’ perception of learning media toward the students listening comprehension skills at the Private Colleges in  Jakarta. Keywords: Learning media; vocabulary mastery; listening comprehension skill